GAMBARAN GEREJA YANG DITERAPKAN PARA KATEKIS KEUSKUPAN SURABAYA DALAM KARYA PASTORAL - Putri Almasari, Lisa Afsari; Ardijanto, Don Bosco Karnan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
This study aims to analyze the understanding of catechists in the Surabaya Diocese regarding the images of the Church and how these images are applied in their pastoral ministry. The research employs a qualitative approach, utilizing online interviews as the primary data collection method, considering the pandemic situation. Informants were selected using a purposive sampling technique, with criteria including official parish appointment, active involvement as catechists, and a minimum of ten years of experience. The findings indicate that catechists perceive the Church through three primary images: the Church as the People of God, as a Community of Communities, and as a Building. Furthermore, in their pastoral ministry, catechists predominantly apply the image of the Church as a community, fostering a sense of unity and collaboration within their congregations. This study contributes to a deeper understanding of the role of catechists in pastoral work and highlights the significance of the Church’s images in shaping their approach to ministry.